Prognosis, Treatment Benefit and Goals of Care: What do Oncologists Discuss with Patients who have Incurable Cancer?. Issue 3 (March 2016) - Raskin, W.; Harle, I.; Hopman, W.M.; Booth, C.M.
Abstract: Aims: Documentation of advance directives among patients with terminal cancer is known to be poor. Here we describe documentation of prognosis, treatment benefit and goals of care discussions in outpatients with advanced cancer. Materials and methods: All patients receiving first-line palliative chemotherapy for metastatic pancreas or lung cancers during 2010–2013 at the Cancer Centre of Southeastern Ontario were identified from electronic pharmacy records. Clinical notes from medical oncology were reviewed to identify documentation of discussions regarding prognosis, treatment benefit and goals of care. Differences between groups were tested using the chi-squared test. Results: In total, 222 patients were included: 80% (177/222) with lung cancer and 20% (45/222) with pancreas cancer. Medical oncology notes documented discussion of prognosis in 64% (142/222), palliative intent of therapy in 82% (182/222), magnitude of treatment benefit in 29% (64/222) and goals of care in 4% (9/222) of patients. An estimate of survival was documented in 36% (79/222) of cases. Across medical oncology providers there was substantial variation in the frequency of discussing prognosis (range 33–90%, P  < 0.001), treatment intent (range 55–100%, P  < 0.001) and goals of care (range 0–17%, P  = 0.034). In total, 41% (93/222) of patients were seen by palliative care; substantial medical oncology provider variation was observed (range 27–58%, P  = 0.020). Referral rates to palliative care did not increase over time (41–44%, P  = 0.250). Conclusions: In this cohort of ambulatory patients with an estimated life expectancy of 1 year or less, medical oncology documentation of prognosis, treatment benefit and goals of care was poor. Less than half the patients were seen by palliative care. Initiatives to improve documentation and referral to palliative care are needed. Highlights: Documentation of advance directives among patients with terminal cancer is known to be poor. In ambulatory patients with an estimated life expectancy of 1 year or less, medical oncology documentation of prognosis, treatment benefit and goals of care was poor. Less than half the patients were seen by palliative care. Initiatives to improve documentation and referral to palliative care are needed.